Defect‐Rich Nitrogen Doped Co3O4/C Porous Nanocubes Enable High‐Efficiency Bifunctional Oxygen Electrocatalysis. (7th June 2019) - Wang, Zhichao; Xu, Wenjia; Chen, Xiaokang; Peng, Yanhua; Song, Yanyan; Lv, Chunxiao; Liu, Hongli; Sun, Junwei; Yuan, Ding; Li, Xiyan; Guo, Xiangxin; Yang, Dongjiang; et al.
Abstract: Heteroatom doping plays a significant role in optimizing the catalytic performance of electrocatalysts. However, research on heteroatom doped electrocatalysts with abundant defects and well‐defined morphology remain a great challenge. Herein, a class of defect‐engineered nitrogen‐doped Co3 O4 nanoparticles/nitrogen‐doped carbon framework (N‐Co3 O4 @NC) strongly coupled porous nanocubes, made using a zeolitic imidazolate framework‐67 via a controllable N‐doping strategy, is demonstrated for achieving remarkable oxygen evolution reaction (OER) catalysis. X‐ray photoelectron spectroscopy, X‐ray absorption fine structure, and electron spin resonance results clearly reveal the formation of a considerable amount of nitrogen dopants and oxygen vacancies in N‐Co3 O4 @NC. The defect engineering of N‐Co3 O4 @NC makes it exhibit an overpotential of only 266 mV to reach 10 mA cm −2, a low Tafel slope of 54.9 mV dec −1 and superior catalytic stability for OER, which is comparable to that of commercial RuO2 . Density functional theory calculations indicate N‐doping could promote catalytic activity via improving electronic conductivity, accelerating reaction kinetics, and optimizing the adsorption energy for intermediates of OER. Interestingly, N‐Co3 O4 @NC also shows a superior oxygen reduction reaction activity, making it a bifunctional electrocatalyst for zinc–air batteries. The zinc–air battery with the N‐Co3 O4 @NC cathode demonstrates superior efficiency and durability, showing the feasibility of N‐Co3 O4 /NC in electrochemical energy devices. Abstract : Defect‐rich nitrogen doped Co3 O4 nanoparticles/nitrogen‐doped carbon framework strongly coupled porous nanocubes (N‐Co3 O4 @NC) are prepared via a simple metal–organic framework‐induced and controllable nitrogen‐doping strategy. Profiting from the considerable amount of nitrogen dopants and oxygen vacancy defects, N‐Co3 O4 @NC behaves as an excellent bifunctional oxygen electrocatalyst, and shows superior efficiency and durability for the as‐assembled zinc–air battery.